1991
DOI: 10.1021/bi00236a032
|View full text |Cite
|
Sign up to set email alerts
|

Orientational distribution of 1,6-diphenyl-1,3,5-hexatriene in phospholipid vesicles as determined by global analysis of frequency domain fluorimetry data

Abstract: Polarized differential phase and modulation ratios were obtained for 1,6-diphenyl-1,3,5-hexatriene (DPH) in 1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC), 1,2-dilauroyl-sn-glycero-3-phosphocholine (DLPC), and 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) vesicles by using multifrequency phase fluorometry. Data were analyzed in terms of both empirical sums-of-exponentials modeling and directly in terms of the orientational distribution functions. The orientational analysis model was used to recover th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
51
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 26 publications
8
51
0
Order By: Relevance
“…Therefore, this model does not seem to be appropriate. This is in agreement with the results reported by Wang et al, 10 Davenport et al, 51 and Lakowicz et al, 54 although other authors found that a multiexponential expression in addition to r ∞ was required for an adequate description of the data. 14,15 The number of components in an experimentally collected anisotropy decay can be influenced by the time-resolved method used, the analysis programs for the data, and the experimental method used for preparing the samples.…”
Section: Experimental and Simulated Decays Associated With Dph In Dppsupporting
confidence: 93%
“…Therefore, this model does not seem to be appropriate. This is in agreement with the results reported by Wang et al, 10 Davenport et al, 51 and Lakowicz et al, 54 although other authors found that a multiexponential expression in addition to r ∞ was required for an adequate description of the data. 14,15 The number of components in an experimentally collected anisotropy decay can be influenced by the time-resolved method used, the analysis programs for the data, and the experimental method used for preparing the samples.…”
Section: Experimental and Simulated Decays Associated With Dph In Dppsupporting
confidence: 93%
“…The membrane location of resveratrol was assessed by steady-state fluorescence quenching and lifetime measurements using DPH and TMA-DPH probes with a known membrane position and depth [33][34][35] 15 . In order to study if the quenching mechanism was static or dynamic, the dynamic quenching constant (K D ) was determined from the slope of the Stern-Volmer plots obtained by lifetime fluorescence measurements (τ o /τ) 15 .…”
Section: Membrane Location Studies By Fluorescence Quenchingmentioning
confidence: 99%
“…DPH is deeply buried in the hydrocarbon core of the lipid bilayer aligned parallel to the acyl chains 33,34 and TMA-DPH is anchored in the polar head region of phospholipids due to its charged group and therefore is located closer to the lipid/water interface 35 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 13 increasing concentrations of resveratrol (quencher). Similar plots were obtained for the other membrane systems with both probes DPH and TMA-DPH, at the same physiological conditions.…”
Section: Resveratrol Location Studiesmentioning
confidence: 99%
“…This mode of operation degrades the spatial resolution of the MCP some what, but signal averaging and spatial correction algorithms reduce this difficulty [9] rotational dynamics of the enzyme [13]. Other applications involve determinations of orientational order parameters in membranes, the orientational distributions [14]. The linked global analysis methods are also powerful in analyzing excited state reactions and energy transfer.…”
Section: Resultsmentioning
confidence: 99%